(untitled) (Research, Society and Development, 2021)
Circumscribing the educational field, this article updates, until 2020, information on the main CAPES programs aimed at reducing asymmetries in the Brazilian National Graduate System (SNPG) and the panorama of postgraduate studies in the Legal Amazon - Brazil, aiming at contribute to the reflections on the asymmetries in the SNPG and the approaches of induction strategies. For this purpose, information available on the CAPES institutional website and on the Sucupira Platform were explored. As a result, there was an evolution of postgraduate studies in the Legal Amazon, which in 2020 concentrated 421 programs; most recent, emerging and in consolidation, highlighting the importance of consolidation policies. It was observed that despite the various public policies aimed at consolidating postgraduate studies and reducing asymmetries, over time, there are still marked differences between the regions of the country, especially in the area comprised by the Legal Amazon.